PENINGKATAN KEMAMPUAN MENULIS PUISI MELALUI METODE PEMBELAJARAN KONTEKSTUAL DENGAN INSPIRATOR CERITA KEPAHLAWANAN PADA SISWA KELAS VIII C SMP PGRI 7 DENPASAR 2023/2024 - Ni Luh Sukanadi; IGA Tuti Indrawati; Rahmi, Rahmi (Bajang Institute, 2024)
In the teaching and learning activities in schools. Language skills are very important to master. Basic skills students need to master is the writing skills. Imagine, writing skills are always present in any learning process. Writing activities related to the field of literature one of which is learning to write poetry. Writing poetry is not just to write a letter or copy, but writing poetry as an aspect of skill feelings. Writing poetry is a process of change in the form of thoughts or feelings into the beautiful form of writing. Thus, to be able to create variations in learning as well as to improve students' skills in writing poetry required a learning model that relates to the real situation (Contextual Teaching and Learning) by inspiration of heroism. this can be seen from the increase in the average value obtained by the students at the beginning of the test (pre-test) the average number of 5.46 with less category, in the first cycle increased the average value of 6.85 with almost enough category, the second cycle increasing the value of the average student to 7.06 with enough categories, and the third cycle is also experiencing an increase in the average value of 7.96 with a student into either category. Based on these results, penulisi formulating such advice, teacher Indonesian SMP PGRI 7 Denpasar order to provide motivation to the students to not neglect the learning literature, especially poetry